Importance vs. Performance: Evaluating the Implementation of Learning from Incidents in Indonesian Construction Industry - Machfudiyanto, Rossy Armyn; Rachmawati, Titi Sari Nurul; Primaputra, Khrisna; Tuasikal, Muhammad Yahya Alfandi; Kim, Sunkuk (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2025)
The construction industry, recognized as one of the most hazardous sectors globally, continues to face escalating challenges, particularly in Indonesia. This sector experiences a yearly increase in workplace accidents, which significantly disrupts economic stability at both micro and macro levels. These incidents lead to substantial economic losses, reduced productivity, and increased medical and compensation costs. To address these risks, the adoption of Learning from Incidents (LFI) has emerged as a critical approach. LFI is a structured process that involves analysing and learning from past incidents to prevent future occurrences, offering a proven methodology to enhance workplace safety. However, despite its potential, the implementation of LFI in Indonesia encounters persistent obstacles. These include a weak safety culture, inadequate reporting systems, and insufficient enforcement of safety standards. Such challenges hinder the effectiveness of LFI and limit its capacity to drive meaningful improvements in construction safety. This study seeks to bridge the gap between the importance and current performance of LFI implementation in the Indonesian construction industry. The research methodology integrates a literature review, expert validation, and Importance-Performance Analysis. Through the literature review and expert validation, critical indicators for LFI implementation were identified, while the Importance-Performance Analysis assessed the alignment of expectations with actual performance as perceived by construction practitioners. Input from three construction safety experts and industry practitioners formed the basis of the analysis. The findings reveal that while Investigation Participation met or exceeded expectations, several other LFI implementation indicators–including Contextual Safety Engineering and Dissemination Reach–require substantial improvement. This consensus highlights significant discrepancies between intended outcomes and actual practices, underscoring the need for targeted strategies to enhance LFI processes. Addressing these gaps can better align LFI implementation with safety objectives, ultimately fostering a safer and more sustainable construction industry in Indonesia.